2009
DOI: 10.1016/j.bbi.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of autoantibodies to neural cells of the cerebellum in the plasma of subjects with autism spectrum disorders

Abstract: Autism Spectrum Disorders (ASD) are a group of heterogeneous, behaviorally defined disorders characterized by disturbances in social interaction and communication, often with repetitive and stereotyped behavior. Previous studies have described the presence of antibodies to various neural proteins in autistic individuals as well as post-mortem evidence of neuropathology in the cerebellum. We examined plasma from children with ASD, as well as age-matched typically developing controls, for antibodies directed aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(137 citation statements)
references
References 53 publications
10
125
1
1
Order By: Relevance
“…A similar result found that children with autism showed positive serum anti-brain reactivity against prenatal rat proteins by western blot, with a different set of banding patterns relative to their non-autistic siblings and other controls (Zimmerman et al, 2007). A 2009 study of plasma from 63 young children with ASD found that 21% of them had antibodies positive against both human and macaque cerebellum samples via western blot, while only one out of the 63 typical developing (TD) controls (2%) tested positive (Wills et al, 2009). When a subset of subject samples was examined via immunohistochemistry (IHC), 21% of those from children with ASD had 'intense immunoreactivity' while none of the TD controls exhibited such reactivity.…”
Section: Anti-brain Antibodies In Children With Asdmentioning
confidence: 99%
“…A similar result found that children with autism showed positive serum anti-brain reactivity against prenatal rat proteins by western blot, with a different set of banding patterns relative to their non-autistic siblings and other controls (Zimmerman et al, 2007). A 2009 study of plasma from 63 young children with ASD found that 21% of them had antibodies positive against both human and macaque cerebellum samples via western blot, while only one out of the 63 typical developing (TD) controls (2%) tested positive (Wills et al, 2009). When a subset of subject samples was examined via immunohistochemistry (IHC), 21% of those from children with ASD had 'intense immunoreactivity' while none of the TD controls exhibited such reactivity.…”
Section: Anti-brain Antibodies In Children With Asdmentioning
confidence: 99%
“…[25][26][27][28] Among the most common findings in ASD subjects and their mothers is an increased presence of autoantibodies directed toward central nervous system proteins. [29][30][31][32][33] In addition, autoantibodies that bind to basement membranes of epithelial cells and colocalize with complement proteins are observed in the intestinal mucosa of children with ASD and GI symptoms. 34 It has been speculated that these autoantibodies could indicate the presence of inflammatory processes and/or an autoimmune component that could affect the integrity of the mucosal barrier and contribute to decreased mucosal barrier integrity; it is also possible that they indicate previous mucosal inflammation.…”
Section: Epidemiology Of Gi Conditions In Asdsmentioning
confidence: 99%
“…Lastly, there is accumulating evidence that the immune system is disrupted in individuals with ASD (Careaga et al, 2010). Elevated levels of chemokines have been detected in the brains and cerebrospinal fluid (Chez et al, 2007;Wills et al, 2009) as well as the plasma (Ashwood et al, 2011a) of individuals with ASD, and this elevation correlated with more impaired behavior (Ashwood et al, 2011b). Furthermore, postmortem studies of individuals with autism also detected presence of activated neuroglial cells in their brain (Vargas et al, 2005).…”
Section: Nachrs Modulate Multiple Behaviors Deficient In Asdmentioning
confidence: 99%